A comprehensive dataset on cytotoxicity of ionic liquids - Liana A. Arakelyan; Daria M. Arkhipova; Marina M. Seitkalieva; Anna V. Vavina; Liliya T. Sahharova; Saniyat K. Kurbanalieva; Alexandra V. Posvyatenko; Ksenia S. Egorova; Valentine P. Ananikov (Scientific Data)
Abstract Ionic liquids (ILs) are structurally tunable salts with applications ranging from chemical synthesis to batteries, novel materials and medicine. Despite their potential, the toxicity of ILs poses significant environmental and biological challenges. This study introduces a comprehensive dataset of cytotoxicity of 1227 ILs, compiled from 151 research papers and encompassing 3837 data entries. For each entry, the following information is provided: substance name, empirical formula, CAS, SMILES, molecular weight, cytotoxicity value, details on the experimental setup (incubation time, cell line, assay used, etc.), and reference to the original publication. This dataset can be used for deriving structure‒activity relationships and establishing the major structural elements that govern the cytotoxic effects of ILs on eukaryotic cells. The dataset is available freely to all researchers.